2018
DOI: 10.1016/j.foodres.2017.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of okara oil for the encapsulation of Lactobacillus plantarum

Abstract: Oil-in-water (O/W) emulsions of okara oil-caseinate (1:2; 1:3 and 1:4 O/W ratios) were used to encapsulate Lactobacillus plantarum CIDCA 83114. Once encapsulated, microorganisms were freeze-dried or spray-dried, and observed by scanning electronic and confocal microscopies. A physical characterization of the dehydrated capsules was carried out by determining their moisture content, water activity, particle size, polydispersity index and zeta potential. Determining the induction times and peroxide values provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
1
9
0
5
Order By: Relevance
“…In this study, the effects of linoleic acid, which is common in daily diets, on the activity of different Lactobacillus strains were studied. The results showed that a certain linoleic acid concentration (50 μg mL −1 ) would affect the activity of various Lactobacillus strains but did not affect the activity of L. plantarum T8, which was consistent with the results of Quintana et al …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the effects of linoleic acid, which is common in daily diets, on the activity of different Lactobacillus strains were studied. The results showed that a certain linoleic acid concentration (50 μg mL −1 ) would affect the activity of various Lactobacillus strains but did not affect the activity of L. plantarum T8, which was consistent with the results of Quintana et al …”
Section: Discussionsupporting
confidence: 91%
“…19 In this study, the effects of linoleic acid, which is common in daily diets, on the activity of different Lactobacillus strains were studied. The results showed that a certain linoleic acid concentration 20 The mechanism by which linoleic acid affects Lactobacillus activity remains unclear. However, linoleic acid and eicosapentaenoic acid exhibit certain antibacterial activities against various food-borne spoilage microorganisms and pathogenic bacteria, 21,22 which are closely related to the cell membrane damage of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…Okara is quick to spoil because of its moisture composition and is therefore treated as animal feed, industrial, or agricultural waste [1]. Dehydrated okara is composed of 55% whole fibre, 21% proteins, 13-14% fats and oils, 1.5% ash and 9-10% moisture [2]. Evidence from a recent study showed that okara insoluble polysaccharides (cellulose, hemicellulose and lignin) have emulsifying and rheological properties [3], and its proteins resemble soy protein isolate [4].…”
Section: Introductionmentioning
confidence: 99%
“…En [47], se evaluó el lactosuero concentrado para aumentar la biomasa y la viabilidad celular en el proceso de secado por atomización de L. plantarum CIDCA 83114. Los microorganismos se cultivaron en caldo MRS a 37 ℃ en condiciones aeróbicas, la fase estacionaria alcanzó un recuento de aproximadamente 13 log 10 UFC/mL.…”
unclassified
“…Los microorganismos se cultivaron en caldo MRS a 37 ℃ en condiciones aeróbicas, la fase estacionaria alcanzó un recuento de aproximadamente 13 log 10 UFC/mL. Esta concentración celular fue la más alta encontrada en la revisión sistemática [47].…”
unclassified